Simulasi Pemanenan Hujan dan Pengaruhnya terhadap Debit Drainase Primer di Jalan Pangeran Samudera, Palangka Raya - I Made Kamiana; Adi Wicaksono; Nomeritae (Jurnal Karajata Engineering, 2024)
Flooding in the residential areas of Palangka Raya City has become more frequent, including in the neighborhoods around Jalan Pangeran Samudera. A viable approach for managing flood risks is the use of rooftop rainwater harvesting. The objective of this study is to model the effects of implementing a rooftop rainwater harvesting system in these residential areas on the flow of the main drainage system. The study was conducted in 2024 using a simulation approach. The data used includes maximum daily rainfall, the drainage network and its flow directions, as well as the roof areas of buildings around Jalan Pangeran Samudera. The Rational Method was employed to analyze the discharge both without and with the rainwater harvesting scenario. The research findings show that, for return periods of 2 to 20 years, the drainage discharge without the implementation of the rooftop rainwater harvesting scenario ranges from 4.414 m³/second to 7.396 m³/second. Meanwhile, with the implementation of the rooftop rainwater harvesting scenario, the drainage discharge is estimated to range from 1.847 m³/second to 3.095 m³/second. In other words, for return periods of 2 to 20 years, the implementation of the rooftop rainwater harvesting scenario is estimated to reduce the drainage discharge by between 2.566 m³/second and 4.300 m³/second. On average, the drainage discharge is expected to decrease by 58.15%.